Exploring wild law : the philosophy of earth jurisprudence - Burdon, Peter (Wakefield Press, 2011)
From cover: "Wild law is a groundbreaking approach to law that stresses human interconnectedness and dependence on nature. It critiques existing law for promoting environmental harm and seeks to establish a mutually enhancing human-Earth relationship. For the first time, this volume brings together voices fromt he leading proponents of wild law around the world. It introduces readers to the idea of wild law and considers its relationship to environmental law, the rights of nature, science, religion, property law and international governance."